Performance of transmission goals in one and two-touch combined team of Ukraine on football in a friendly match in 2011 and the matches of the European Championship in 2012 - Chornobay I.M; Matviiv V.I (Kharkov National Pedagogical University, 2013)
The aim of the study is to determine the performance of the transmission ball in one and two-touch athletes Ukrainian National Team. The material for the study included a video of friendly and official matches of the Ukrainian team at the European Championships in 2012. It is established that the team performed for the match 78 - 63 gears with one touch (replication error - 20.51% - 34.72%) and 124 - 107 gears in two touches (replication error - 10.28% - 17.79%). It is noted that the lower estimate corresponds to the transmission rate of less than 100 goals in one touch of the match. Team deserves high marks, performing over 130 such programs ball per game. Ukrainian national team in 2011, served an average of 125 per game gear ball in two touches. More gear ball with one touch in 2012 Ukrainian performed in the game against England - 78 assists. It is noted that the figures obtained passes of ball team of Ukraine are the basis for the preparation of the appropriate correction for the next match.